Pengawasan Preventif Melalui Harmonisasi Pembentukan Peraturan Daerah Terhadap Eksistensi Regulasi Muatan Lokal Dalam Otonomi Daerah - Arifin, Firdaus; Maarif, Ihsanul (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2024)
The harmonization process in the formation of regional regulations in Indonesia is designed to ensure alignment between local regulations and national law. However, the centralistic approach often adopted in this harmonization process tends to limit the flexibility of local governments in formulating regulations that suit local needs. This issue raises concerns that the constitutionally granted authority of local governments to create localized regulations may be eroded. This study aims to analyze the impact of a centralistic harmonization approach on the effectiveness of regional autonomy, particularly in the context of local regulation. Using a normative juridical method with a descriptive-analytical approach, this research evaluates legislation, legal documents, and related literature to understand the implications of harmonization on local regulations. The findings indicate that overly centralistic harmonization can hinder innovation and adaptation of local regulations, reducing the capacity of local governments to respond to the needs of their communities. These findings emphasize the need for a more flexible and inclusive harmonization procedure to ensure that local regulations can still function effectively within the national legal framework. The implications of this study suggest that a more balanced approach between centralization and decentralization is necessary to maintain sustainable, adaptive, and responsive regional autonomy.